Norwegian consumers’ willingness to try food made from insects: The role of trust, food choice motives and OCEAN personality traits - Sarah Wangui Muiruri (Journal of Agriculture and Food Research)
Entomophagy, the consumption of insects, may reduce the negative health and environmental impacts of meat. As one of the novel protein alternatives expected to replace conventional meat consumption, its success will depend on consumer acceptance. To investigate the consumer acceptance of entomophagy, three rounds of a Norwegian survey with 8633 useable responses conducted in 2019/2020, 2021/2022, and 2023/2024 were used. Generalized structural equation modelling was used to test the developed hypotheses. The direct effects of trust, food choice motives, and OCEAN personality traits were investigated. The mediating effects of food safety concerns on the relationship between trust and willingness to try (WTT) food made from insects were also investigated. Social trust and trust in food authorities were positively associated with WTT. No association was found for trust in retailers. Negative associations were found between the effects of social trust and trust in food authorities on food safety concerns, and food safety concern was also a significant mediator. Respondents who emphasized environmental friendliness, health, and novelty were more willing to try, and those who emphasized natural ingredients and familiarity were less willing. Openness was positively associated with WTT, while conscientiousness, extraversion, and agreeableness had a negative association. Gender, education, age and urban living were also found as significant moderators in some paths. The findings of the study imply the need to foster trust among consumers and to emphasize the environmental and health benefits of entomophagy while focusing on increasing consumer familiarity and use of natural ingredients. Personality-focused marketing strategies may also be implored to target consumers high in openness and low in conscientiousness, extraversion, and agreeableness.